BS EN 62841-3-6 AMD AB. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 3-6. Particular requirements for transportable diamond drills with liquid system (28th January 2021) - British Standards Institution,
No abstract available